2020
DOI: 10.3390/ijerph17239054
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of Internet Poker Players on Harm-Reduction Strategies: A Cross-Sectional Study

Abstract: Background: Internet gambling may increase rates of gambling harm. This current study aimed to assess Internet poker players’ views on various harm-reduction (HR) strategies. It also examined differences in these views according to the games played (poker only vs. poker plus other gambling activities), indebtedness, and problem gambling severity. Methods: Internet poker players (n = 311; 94.2% Male) recruited online between 2012 and 2014 were included in the analyses and completed a survey on indebtedness, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…Response options were “no money gambled online, only offline,” “1–25% online,” “26–50% online,” “51–75% online,” “76–90% online,” “≥91% online.” The proportion of money gambled was chosen as a proxy for the importance of gambling activities. This agreed with a study showing that online gamblers considered money limits to be one of their most important harm reduction strategies (above time limits) ( 18 ). Furthermore, numerous studies have reported on problems related to money and indebtedness among online gamblers ( 19 21 ).…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Response options were “no money gambled online, only offline,” “1–25% online,” “26–50% online,” “51–75% online,” “76–90% online,” “≥91% online.” The proportion of money gambled was chosen as a proxy for the importance of gambling activities. This agreed with a study showing that online gamblers considered money limits to be one of their most important harm reduction strategies (above time limits) ( 18 ). Furthermore, numerous studies have reported on problems related to money and indebtedness among online gamblers ( 19 21 ).…”
Section: Methodssupporting
confidence: 89%
“…Apart from their risks, online gambling environments may also provide good opportunities to promote responsible gambling using tools that can be personalised to the individual gambler ( 7 ). It could also be an environment in which to develop and offer a wide range of gambling-related harm-reduction strategies ( 18 ). From a public health perspective, it will be important to monitor further developments in online and offline gambling and to adapt future policies to reduce the impact of online and offline gambling on public mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies focused on the impacts of personalised feedback [51,52,55,56] and/or personal contact between counsellors and people who gamble [57][58][59][60][61][62]. Jonas et al, (2020) found that personal contact with counsellors in conjunction with other responsible gambling type interventions had the greatest impact on longterm reduction in problem gambling scores.…”
Section: Secondary Preventionmentioning
confidence: 99%